Between myth and reality. The situation of the mysterious Elizabeth Island of Francis Drake Entre el mito y la realidad. La situación de la misteriosa Isla Elizabeth de Francis Drake - Martinic B, Mateo (My University, 2019)
In 1578, after a calm navigation through the Strait of Magellan, the English sailor Francis Drake had to face the furies of the South Pacific Ocean for almost two months. In one of his forced derivations the endless storm that punished his ship took him deep into the stormy southern sea, circumstance in which he and his companions found an island that they called Elizabeth fixing its approximate position. That island would never again be sighted by any sailor until now. Posterity has accepted this observation and has sought an explanation for its disappearance attributing it to the dynamics of the earth's crust, which in turn causes variations in the ocean floor. It is here reported the progressive knowledge of submarine relief in the Drake Sea area south of the Diego Ramírez Islands, where the Sars submarine mount has recently been found, an abyssal elevation as interesting as suggestive for further scientific studies referring to the interconnection of Antarctica and South America in remote geological times.
Keywords: abyssal dynamic; drake sea; elizabeth island; southern pacific ocean; submarine mount sars